Autism Spectrum Disorder and Childhood Education: what the dissertations of Postgraduate programs in Education say (Research, Society and Development, 2022)
The purpose of this work is to map some of the academic productions, in the master's dissertation modality, carried out in the last five years with the descriptors autism and/or Autistic Spectrum Disorder (ASD) and Early Childhood Education. We are based on the analysis of abstracts of dissertations in Graduate Programs in Education (2016 to 2020). The research had an analytical-descriptive character based on the following method: a survey carried out in the portals of Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel (CAPES) and the Brazilian Digital Library of Theses and Dissertations. Once the research object was found, the floating reading was carried out, the procedures for exploring the texts were carried out, and the registration and context units were formatted. Then, the description of the nuclei of meaning was passed. In the results, pluralities of sub-themes were found, namely: school inclusion of children with ASD, routine activities of autistic students, family-school relationship, maternal subjectivity of children with ASD, inclusive public educational policies for autistic children, teacher training and possibilities collaborative training, among others. In general, the productions indicate that there are still great difficulties in promoting inclusive education for children with ASD, especially due to the absence of training public policies for education professionals and poor accessibility (material and architectural). Finally, the work suggests that successful public policies and pedagogical practices need to be more assertive to this target and that educational institutions should have a more specific look at investment in all public areas for children with ASD.